SAOCOM-1 L-band DInSAR Time Series generation through the P-SBAS approach: algorithm extension and products analysis - De Luca, Claudio (2024)
We present in this work the new advances of the Differential SAR Interferometry (DInSAR) technique referred to as Parallel Small BAseline Subset (P-SBAS) approach, for the generation of displacement time series from the recently available L-band SAR image sequences acquired by the Argentinian SAOCOM-1 constellation. In particular, we first discuss the algorithmic extensions allowing us to retrieve SAOCOM-1 DInSAR products, with a main focus on the exploitation of Stripmap SAR images and multi-look interferograms. These algorithmic improvements are relevant to the adjacent Single Look Complex (SLC) image slices merging, to the multi-temporal residual orbital artifacts mitigation and to the phase unwrapping procedure enhancement. Subsequently, the effectiveness of the extended P-SBAS processing chain is shown through a comparative analysis between the achieved SAOCOM-1 DInSAR results and the corresponding ones relevant to Sentinel-1 and COSMO-SkyMed acquisitions. Moreover, a comparison between the SAOCOM-1 displacement time series and the GNSS measurements, relevant to the Campi Flegrei caldera (Italy), is presented. This shows that the mean standard deviation value of the differences between the DInSAR and the GNSS time series, the latter projected in the radar line of sight, is of about 1 cm, further confirming the effectiveness of the P-SBAS processing chain extension.